Topical Application of Liriope platyphylla Extract Attenuates Dry Eye Syndrome Induced by Particulate Matter - Su Jeong Song; Soo-Wang Hyun; Tae Gu Lee; Bongkyun Park; Kyuhyung Jo; Ik Soo Lee; Chan-Sik Kim (Journal of Ophthalmology)
Particulate matter (PM) is a type of air pollutant that poses a risk to human health. In the ocular system, PM causes or aggravates dry eye syndrome (DES) by damaging the corneal and conjunctival epithelia. Liriope platyphylla has been used traditionally as an expectorant, antitussive agent, and tonic in Korea. However, the effects of Liriope platyphylla extract (LPE) on PM-induced ocular damage have not been elucidated. In this study, we evaluated the in vivo protective effect of LPE against PM-induced DES in rats. Topical administration of LPE attenuated the PM-induced decrease in tear volume and reduced corneal epithelial irregularity and damage. LPE also protected against PM-induced disruption of the corneal mucin-4 layer and reduction in the conjunctival goblet cell density. These findings suggest that LPE has protective effects against PM-induced DES.